Quality Management: knowledge of nurses working in hemodialysis (Research, Society and Development, 2021)
In the healthcare area, quality management is related to project administration of systems, policies and processes that reduce and even extinguish the damage that can occur to the patient, improving care. Nurses are essential professionals in the management and care provided to patients, their satisfaction and the general quality of care must involve elements that combine effective care and results with excellence in this care. This study aimed to analyze the knowledge of nurses working in hemodialysis on quality management. It is a field research, exploratory and descriptive, with a qualitative approach, through the study of multiple cases. Nurses who work in four hemodialysis clinics located in the east side of the city of São Paulo participated in the research. The analysis of the collected data was carried out through the transcripts of the interviews and analysis of the subject's speech, the results were presented in general summary tables of the comments. It was possible to notice that nurses describe quality management in hemodialysis as an important strategy that helps care, optimizes work processes involving the various professionals who work in this segment. However, knowledge about quality management is mentioned in a fragmented and non-uniform way, even for nurses who work in the same hemodialysis clinic.